The Contribution of Scientific Argumentation to Critical Thinking Skills: A Literature Review - Damarsha, Adrian Bagas; Naufal, Muhammad Ghiyats; Suprapto, Nadi; Hariyono, Eko; Nisa', Khoirun; Ariana, Indri Maya; Faradillah, Khofifatur Risma (National Dong Hwa University, 2024)
This study offers an evaluation of previous research that shows the importance of argumentation learning in science to improve critical thinking through bibliometrics. This study aims to describe the trend, contribution, and stages of argumentation strategies in science to improve critical thinking skills. The research method used is a bibliometric study and a systematic literature review. The data that met the requirements in this study were 257 documents from Scopus. The results obtained indicate that argumentation research in science to improve critical thinking skills continues to increase. One of the countries that contributed to this study was Indonesia. Research findings indicate that argumentation is effective in improving critical thinking skills through pattern analysis. This is evidenced by the results of a literature review that scientific argumentation patterns can improve critical thinking skills through real-world problems by providing several reasons. Thus, it can be concluded that argumentation in science learning can improve critical thinking skills through experienced facts. This research is expected to contribute to the importance of argumentation in science education, understand current research trends and contributions, and encourage the implementation or development of argumentation-based learning strategies.